A single amino acid in the F2 subunit of respiratory syncytial virus fusion protein alters growth and fusogenicity - Lawlor, Heather A.; Schickli, Jeanne H.; Tang, Roderick S. (Journal of general virology, 2013)
Respiratory syncytial virus (RSV) causes severe lower respiratory tract infection in children, especially in infants less than 1 year of age. There are currently no licensed vaccines against RSV. rA2ΔM2-2 is a promising live-attenuated vaccine candidate that is currently being evaluated in the clinic. Attenuation of rA2ΔM2-2 is achieved by a single deletion of the M2-2 gene, which disrupts the balance between viral transcription and replication. Whilst performing a manufacturing feasibility study in a serum-free adapted Vero cell line, differences in growth kinetics and cytopathic effect (CPE) were identified between two rA2ΔM2-2 vaccine candidates. Comparative sequence analysis identified four amino acid differences between the two vaccine viruses. Recombinant rA2ΔM2-2 viruses carrying each of the four amino acid differences identified a K66E mutation in the F 2 fragment of the fusion (F) protein as the cause of the growth and CPE differences. Syncytium-formation experiments with RSV F protein carrying mutations at aa 66 suggested that a change in charge at this residue within the F 2 fragment can have a significant impact on fusion.